The underwater city : Bionicle, Volume 6 - Farshtey, Greg; Sayger, Stuart; Zanier, Christian (New York : Papercutz, 2009)
After its discovery by an inventor named Defilak, the Mask of Light begins to reveal a deadly secret that becomes apparent to those who witness its effects on the user. For while its power gives the wearer great strength that could be used for good, the Mask of Light or "Ignika" as it comes to be called, brings paranoia, jealousy, and madness to anyone who wears it. The struggle for the Mask of Light continues.